Prevalence and factors associated with newborn care practices among caregivers: a protocol for systematic review and meta-analysis in sub-Saharan Africa - Solomon Mohammed Salia; Amidu Alhassan; Billie de Haas; Jelle Stekelenburg; Robert Kaba Alhassan (Discover Public Health)
Abstract Introduction Between 1990 and 2022, the global under-five and neonatal mortality rates decreased by 62% and 56%, respectively. However, neonatal mortality is still on the rise in sub-Saharan Africa. Despite the WHO essential newborn care package to improve newborn care practices and reduce neonatal mortality, the COVID-19 pandemic has impacted newborn care practices globally. After the pandemic, ascertaining the magnitude of newborn care practices and factors associated with these practices among caregivers is essential. However, no systematic reviews or meta-analyses on this topic in SSA have been published since 2021. This paper reviews the prevalence and determinants of newborn care practices among caregivers in sub-Saharan Africa. Methods and analysis The PRISMA-P guidelines will be used to report the systematic review and meta-analysis protocol. An online search on electronic databases such as CIHNAL, Scopus, PubMed, Web of Science, Google Scholar, and AJOL will be conducted from January 2021 to present to identify relevant academic, peer-reviewed quantitative studies published in English Language. Medical Subject Headings will aid in identifying keywords pertinent to the study's concepts, combined with Boolean operators to obtain suitable articles. Two independent authors will review the articles’ abstracts and titles and conduct full article screening for inclusion. Data will be analyzed using narrative synthesis for nonhomogeneous data while homogenous data will be analyzed using meta-analysis including odds ratios and confidence intervals. Ethics and dissemination Ethical approval is not required for systematic reviews. Results will be disseminated through publication in a peer-reviewed journal. Systematic review registration This systematic review and meta-analysis is registered with the PROSPERO International Prospective Register for Systematic Reviews with the registration number CRD42024510159.